The prevalence of exposure to domestic violence and the factors associated with co-occurrence of psychological and physical violence exposure: a sample from primary care patients - Kersnik Janko; Pesjak Katja; Selic Polona (BMC Public Health, 2011)
Abstract Background Since many health problems are associated with abuse and neglect at all ages, domestic violence victims may be considered as a group of primary care patients in need of special attention. Methods The aim of this multi-centre study was to assess the prevalence of domestic violence in primary care patients, and to identify those factors which influence the co-occurrence of psychological and physical violence exposure and their consequences (physical, sexual and reproductive and psychological) as obtained from medical records. A study was carried out in 28 family practices in Slovenia in 2009. Twenty-eight family physicians approached every fifth family practice attendee, regardless of gender, to be interviewed about their exposure to domestic violence and asked to specify the perpetrator and the frequency. Out of 840 patients asked, 829 individuals, 61.0% women (n = 506) and 39.0% men (n = 323) were assessed (98.7% response rate). They represented a randomised sample of general practice attendees, aged 18 years and above, who had visited their physician for health problems and who were given a physical examination. Visits for administrative purposes were excluded. Multivariate binary logistic regression analysis was used to determine the factors associated with exposure to both psychological and physical violence. Results Of 829 patients, 15.3% reported some type of domestic violence experienced during the previous five years; 5.9% reported physical and 9.4% psychological violence; of these 19.2% of men and 80.8% of women had been exposed to psychological violence, while 22.4% of men and 77.6% of women had been exposed to physical violence. The domestic violence victims were mostly women (p < 0.001) aged up to 35 years (p = 0.001). Exposure to psychological violence was more prevalent than exposure to physical violence. Of the women, 20.0% were exposed to either type of violence, compared to 8.0% of male participants, who reported they were rarely exposed to physical violence, while women reported often or constant exposure to physical violence. Their partners were mostly the perpetrators of domestic violence towards women, while amongst men the perpetrators were mostly other family members. In univariate analysis female gender was shown to be a risk factor for domestic violence exposure. Regression modelling, explaining 40% of the variance, extracted two factors associated with psychological and physical violence exposure: the abuse of alcohol in the patient (OR 4.7; 95% CI 1.54-14.45) and their unemployment (OR 13.3; 95% CI 1.53-116.45). Conclusions As far as the study design permits, the identified factors associated with both psychological and physical violence exposure could serve as determinants to raise family physicians' awareness when exploring the prevalence of domestic violence. The results of previous research, showing at least 15% prevalence of exposure to domestic violence among primary care patients in Slovenia, and the female gender as a risk factor, were confirmed.